Analisis Dampak Kualitas Produk, Promosi dan Brand Image Terhadap Loyalitas Konsumen Teh Botol Sosro di Kota Medan - Nur Fatdillah; Tika Nirmala Sari (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2026)
This study aims to analyze the impact of Product Quality, Promotion and Brand Image on Consumer Loyalty of Teh Botol Sosro in Medan City. This study uses a quantitative method with an associative approach. The location of this study was conducted in five sub-districts in Medan City, namely: Medan Marelan, Medan Belawan, Medan Deli, Medan Area and West Medan. The sample collection technique used was Purposive Sampling using the Lameshow formula with a sample size of 120 respondents. The results of the study indicate that partially Product Quality does not have a positive and significant effect on Consumer Loyalty with a t-count value < t-table of 0.861 < 1.980. Promotion partially has a significant and positive effect on Consumer Loyalty with a t-count value < t-table of 2.407 > 1.980. Brand Image has a positive and significant effect on Consumer Loyalty with a t-count value < t-table of 6.638 > 1.980. Furthermore, the results of the F test show that the quality of promotional products and brand image simultaneously have a positive and significant effect on Consumer Loyalty of Teh Botol Sosro in Medan City with a calculated F value < F table of 2.407 > 1.980